Survival analysis among lung cancer patients in Pahang - Ng, Teck Han; How, Soon Hin; Kuan, Yeh Chunn; Ab Rahman, Jamalludin; Abdul Rani, Mohammed Fauzi (Wiley-Blackwell, 2010)
November 2009. Patients with histology confi rmed lung cancer were recruited in the study. Survival time was defi ned from the date of histological diagnosis to time of death. Data on patients’ characteristic, ECOG functional status, staging, treatment were obtained. Kaplan Meier was used to measure the survival status and compared using log-rank test. Relevant factors were included in Cox Proportional Hazard Regression to identify independent factors affecting the survival of lung cancer patient. Results Of a total of 100 patients enrolled in this study, 81% were males and 82% were smokers. The age ranges from 30 to 83 years with mean (SD) age of 59.6 (11.3) years. There were 68 Malays, 27 Chinese, 3 Indians and 2 Arbogines. ECOG of 0 or 1, 2 and 3 or 4 were found in 47%, 19% and 34% respectively. All patients presented with either stage 3 or 4 (47% in stage 4). Only 45% patients received conventional chemotherapy. Overall, median (SE) survival was 14.8 (3.5) weeks. There were no signifi cant differences in median survival among males vs females, smokers vs non-smokers, Malays vs non- Malays, stage 3 vs stage 4. However, patients with ECOG 0 or 1 had longer median survival than patients with ECOG 2 or more (35.3 week vs 8.9 weeks, p < 0.001). Patients given chemotherapy also had longer median survival than those without chemotherapy (37.4 weeks vs 4.9 weeks, p < 0.001). On multivariate analysis, when all these factor were included in the regression model, only smoker and patients on best supportive care alone were the signifi cant independent negative prognostic factors affecting survival. Conclusion Patients of good performance status of ECOG 0/1 and given chemotherapy were associated with better survival in lung cancer patients.